EFFECTIVENESS OF COMPREHENSIVE NURSING STRATEGIES ON STATE ANXIETY AMONG PATIENTS SUBJECTED TO CABG SURGERY (International Journal of Food and Nutritional Sciences, 2022)
Coronary Artery Bypass Grafting (CABG) surgery, a common treatment for coronary artery disease, often induces significant anxiety in patients. Elevated state anxiety levels can negatively impact the overall surgical experience, recovery, and outcomes. Comprehensive nursing strategies, including psychological interventions and holistic patient care, have been identified as potential mitigators of perioperative anxiety. This study investigates the effectiveness of a tailored set of comprehensive nursing strategies in alleviating state anxiety among patients undergoing CABG surgery. A randomized controlled trial was conducted involving a sample of CABG patients. The experimental group received personalized nursing interventions, including preoperative education, relaxation techniques, therapeutic communication, and postoperative support, in addition to standard care. The control group received routine care. State anxiety levels were measured using validated anxiety assessment tools preoperatively, postoperatively, and during the follow-up period. This study provides compelling evidence for the effectiveness of comprehensive nursing strategies in managing state anxiety among patients undergoing CABG surgery. By addressing the psychological aspects of the perioperative period, nurses play a vital role in enhancing the overall patient experience and potentially improving clinical outcomes